Profiles of caregiver burden among adolescents with non-suicidal self-injury: a latent profile analysis - Qin, Yuan; Liu, Jiao; Duan, Jiming; Yang, Bo (Frontiers in Psychiatry, 2025)
BackgroundNon-suicidal self-injury (NSSI) in adolescents represents a significant global public health challenge, with lifetime prevalence rates demonstrating a consistent upward trajectory. Current evidence indicates that NSSI conveys elevated risks for both physical complications and psychological comorbidities, while simultaneously imposing a substantial burden on primary caregivers.ObjectiveThis study applied latent profile analysis (LPA) to classify distinct caregiver burden profiles among adolescents with NSSI, identify modifiable determinants, and establish an empirical foundation for developing precision interventions stratified by burden type.MethodFrom August 2022 to May 2023, 385 caregivers of adolescents with NSSI in Sichuan Province, China, were selected as respondents and systematically assessed using six validated instruments: General Information Questionnaire, Family Burden Scale of Disease, Social Support Rating Scale, Generalized Anxiety Disorder 7-Item Scale, Patient Health Questionnaire-9, and Internalized Stigma of Mental Illness Scale. LPA with maximum likelihood estimation identified distinct caregiver burden profiles, and multinomial logistic regression to determine predictors of profile membership.ResultsThe caregiver burden among adolescents with NSSI can be identified into three profiles: low burden-family vulnerability profile (34.5%), moderate burden-mental health priority profile (36.6%), and high burden-economic preponderance profile (28.9%). Female caregivers (OR = 3.760, p = 0.005), rural residents (OR  =  3.666, p  =  0.027), diminished social support (OR  =  0.884, p  =  0.016), and elevated anxiety severity (OR  = 1.183, p = 0.027) exhibited heightened vulnerability to the moderate burden-mental health priority profile. Heightened depression symptoms (OR = 1.130, p = 0.037) and stronger illness-related stigma (OR = 1.063, p = 0.001) were disproportionately represented in both moderate burden-mental health priority profile and high burden-economic preponderance profile.ConclusionsThis study delineates three distinct caregiver burden profiles among adolescents with NSSI, alongside sociodemographic and clinical predictors of profile membership. Tailored interventions, such as rapid mental health service linkage for high-burden subgroups and family-centered psychoeducation, can mitigate these burdens through stratified support mechanisms.